Photosynthesis-dependent H2O2 transfer from chloroplasts to nuclei provides a high-light signalling mechanism - Marino Exposito-Rodriguez (Nature Portfolio, 2017)
Multiple plastid-derived signals have been proposed but not shown to move to the nucleus to promote plant acclimation to fluctuating light. Here the authors use a fluorescent hydrogen peroxide sensor to provide evidence that H2O2 is transferred directly from chloroplasts to nuclei to control nuclear gene expression.